Integrated problem-based learning versus lectures: a path analysis modelling of the relationships between educational context and learning approaches. Issue 1 (1st January 2018) - Gustin, Marie-Paule; Abbiati, Milena; Bonvin, Raphael; Gerbase, Margaret W.; Baroffio, Anne
ABSTRACT: Students' approaches to learning are central to the process of learning. Previous research has revealed that influencing students' approaches towards deep learning is a complex process and seems much more difficult than expected, even in student-activating learning environments. There is evidence that learning approaches are impacted not only by the learning environment, but also by how students perceive it. However the nature of the links between the environment itself, the way in which it is perceived by students and students' learning approaches is poorly understood. This study aimed at investigating the relationships between students' perception of their educational context and learning approaches in three learning environments differing by their teaching formats (lecture or problem-based-learning PBL) and integration level of the curriculum (traditional or integrated). We tested the hypothesis that a PBL format and an integrated curriculum are associated to deeper approaches to learning and that this is mediated by student perception. The study sample was constituted of 1394 medical students trained respectively in a traditional lecture-based ( n  = 295), in an integrated lecture-based ( n  = 612) and in an integrated PBL-based ( n  = 487) curricula. They completed a survey including the Dundee-Ready-Educational-Environment-Measure (students' perceptions of the educational environment) and the Revised-Study-Process-Questionnaire (learning approaches). Data were analysed by path analysis. The model showed that the learning environment was related to students' learning approaches by two paths, one direct and one mediated via students' perception of their educational context. In the lecture-based curricula students' used deeper approaches when it was integrated and both paths were cumulative. In the PBL-based curriculum students' did not use deeper approaches than with lectures, due to opposite effects of both paths. This study suggested that an integrated lecture-based curriculum was as effective as a PBL curriculum in promoting students' deep learning approaches, reinforcing the importance of integrating the curriculum before choosing the teaching format.